PENGARUH BRAND IMAGE TERHADAP MOTIVASI DAN MINAT WISATAWAN DOMESTIK BERKUNJUNG KE SANUR VILLAGE FESTIVAL - Pandu Fariska, I Gusti Putu; Sasrawan Mananda, I Gusti Putu Bagus; Susrami Dewi, Ni Gusti Ayu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 7 No 2 (2019): Jurnal IPTA (December 2019), 2019)
Sanur Village Festival is an event established by the Yayasan Pembangunan Sanur which combines large-scale activities consisting of food festivals, a series of contests, competitions, cultural arts attractions, music, and a variety of friendly activities environment. Samples of this study were domestic tourists who have visited the Sanur Village Festival. The sampling technique used purposive sampling in 160 respondents. Data collection techniques are performed with observations, questionnaires, interviews, literature studies, and documentation. The sampling technique uses the purposive sampling technique and utilizes a likert scale model questionnaire that is calibrated using the validity test and the reliability test is calculated using the Cronbach alpha coefficient using the SPSS 25.0. The data analysis techniques in this study used partial least square analysis techniques (PLS), and the equation model will analyzed is the outer model, inner model and hypotheses testing. Based on the software calculation smartPLS version 3.0 obtained the result that there is a significant influence between the variable brand image to the motivation and interest of domestic tourists visit to Sanur Village Festival. This is evidenced by the results of the analysis of the influence of the brand image to the motivation obtained value of 41.9%, while the interest earned a value of 40.5%. Furthermore, the influence of motivation to interest can be seen from the results of the analysis of Partial Least Square obtained T-Statistic of 1.766 > T-table 1.654, this means the motivation variable positively affect the interest of domestic tourists visiting Sanur Village Festival.